(untitled) (Research, Society and Development, 2021)
Objective: To analyze the scientific evidence available in the literature on the importance of play therapy practices in pediatric hospital units, only in the Brazilian scenario. Materials and Methods: An integrative review study, with a qualitative and narrative approach, data collection was carried out from January to June 2021. Indexed publications were collected in the following databases: LILACS, BDENF and SCIELO. Data were tabulated and organized in Microsoft Excel, and then a descriptive analysis of the information was performed, and expressed in graphs and tables. Results and Discussion: Evidenced that there is still a great devaluation of this activity, both by professionals and institutions, not providing support, investment or encouragement for the inclusion of this practice in the child care routine. In this way, playful moments are always left in the background and pediatric patients often end up acquiring only negative experiences during their hospital stay. Conclusion: we emphasize the need for new studies that debate more on this topic, in order to increase the attention of the target audience and expand the number of more up-to-date research and interventions. It is necessary to carry out training for academics and professionals in the area, so that play therapy is seen as something inherent and inseparable from child care. Since playful activities bring benefits not only for the hospitalized child, but also for their companion, for the institution and for the health team that is providing assistance, providing a more humane and qualified pediatric care.